Uma avaliação política da política de avaliação da educação superior brasileira - Lopes, Pedro Isaac Ximenes (2013)
We had as the problem of analysis in this research: what are the assumptions, principles and general content that based the Sistema Nacional de Avaliação da Educação Superior (SINAES). We started from the hypothesis that the general content of SINAES is essentially based on the assumptions and principles of a control/regulatory perspective of evaluation and a summative epistemology, objectivist and quantitativist, constituted by members who prioritize testing and classification of courses and institutions based on market values. The overall goal was to make a political evaluation of SINAES and the specific objectives were: a) apply the concepts of politics evaluation and meta-evaluation, b) identify the role of international organizations in education reform in the 1990s and its impact on superior education in Brazil c) redeem the concept of evaluation, especially in the field of studies in education; and d) investigate the evaluation policies of Brazilian superior education leading to SINAES. As for the technical procedures for collecting and analyzing data, the research was made with bibliography and documents, considering that it was developed by bibliographic sources and official publications. It was developed by crossing sources: texts or documents remitted to others; it was also concentrated: on the role of international organizations in educational and State reforms (in the 1990s); on the policies of evaluation of the Brazilian superior education (1980s and 1990s); on the proposal of the Comissão Especial de Avaliação (CEA); on the Law No. 10.861/2004; on the documents of CONAES; on the Decree No. 5.773/2006, and the MEC Regulatory Ordinances No. 4/2008 and No. 12/2008. It did not stop in the so called purely technical aspects, but in the ideological field itself. The research found that international organizations, notably the World Bank, played a political, intellectual and financial role determinant to the field of education, a fact that reflects in the legal framework. It was also found that the politics of evaluation of the superior education is historically marked by conflict, represented by two distinct perspectives of different natures and emphases. On one hand, the focus is on control / regulation, favoring efficiency, productivity and competitiveness benchmarking and prioritizing the punctual performance and measurement. On the other, it seeks to transform academic perspective in primarily formative / emancipatory, in order to support more institutional improvement. It was concluded that the CEA presented a conception evaluation predominantly formative and emancipatory, which emphasized the idea of system, centered around the institution and repudiated the rankings practices. In the post-formulation period, however, some of its principles were fragmenting and, gradually, the institution was giving way to the courses and the Exame Nacional de Desempenho de Estudantes (ENADE) grew in prominence. With the creation of the Conceito Preliminar de Cursos superiores (CPC) and of the Índice Geral de Cursos da Instituição de Educação Superior (IGC), it was redemeed the practice of evaluation as measurement and control, under the principles of efficiency and productivity. So, SINAES that seemed like a progressive evaluation method has assumed a setting that close resembles the Exame Nacional de Cursos (ENC-Provão). Nevertheless, the survival of institutional formative evaluation, in the superior education evaluation policies, still an issue in dispute